Exploring racial and gender discrimination: A sociological study of Leila Slimani’s In the Country of Others - Rizqi, Ella Fahrur; Syamsuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
One of the prominent social issues today is discrimination, depicted in various literary works. This study examines the forms and causes of discrimination against female characters in Leila Slimani’s novel, employing Pettigrew’s discrimination theory and a sociology of literature approach as well as Wellek and Warren’s literary sociology approach. Those theories are utilized as a method of sociology-focus approach to analyze some quotes which depicts the discrimination. In the end, this study found that female characters in the story face direct discrimination through citizenship status and race. Besides, the characters also suffered physical attacks, as well as gender and indirect discrimination through property ownership restrictions and marriage regulations. Pettigrew's theory attributes these discriminatory acts to prejudice and stereotypes.